Effect of glucocorticosteroid injections in tennis elbow verified on colour Doppler ultrasonography: evidence of inflammation. Issue 12 (28th February 2008) - Torp-Pedersen, T E; Torp-Pedersen, S T; Qvistgaard, E; Bliddal, H
Abstract : Objectives: It has previously been reported that lateral epicondylitis may be diagnosed with colour Doppler ultrasonography (US) by detecting hyperaemia inside the common extensor origin (CEO).This study reports on the association between Doppler US findings and the short-term response of US-guided corticosteroid injection in patients with LE. Design: Case-only, blinded intervention study. Setting: Secondary care at a government hospital. Patients: 62 patients with LE verified by colour Doppler US. Intervention: One US-guided corticosteroid injection was given into the CEO. Main outcome measures: Patients were evaluated at baseline before the injection and at 2 weeks of follow-up. Outcome measures were changes in pain score and US parameters (resistive index (RI) and the amount of colour within the CEO). Prognosticators for outcome were: use of computer mouse, symptom duration, elbow strain, RI, colour fraction, Likert pain score, pain at rest, pain during activity, age, height, weight, disease in dominant versus nondominant arm. Results: All but one patient experienced improvement of general elbow pain perception at follow-up at 2 weeks. In parallel, Doppler US showed significant reduction in colour fraction (mean (standard deviation) with 95% confidence limits: baseline 0.14 (0.10), at follow-up 0.02 (0.02), p<0.0001). All but five patients showed a decrease in colour fraction; 74% decreased to 0. No clinical or US parameter could distinguish responders from non-responders. Conclusion: Corticosteroid injection has a marked short-term effect on pain and Doppler parameters. The reduction in hyperaemia mediated by an anti-inflammatory drug can be interpreted as evidence of an inflammatory component in LE.